Evaluation of radar reflectivity-rainfall rate, Z-R relationships during a stratiform event in the tropics - Sobli, Nuurul Hudaa; Ismail, Ahmad Fadzil; Asnawi, Ani Liza; Saad, Wahida (2013)
Abstract—A number of factors can certainly affect the accuracy of Z-R relationships; including poor hardware calibration. The inaccuracy might also be due to the differences between the ground-level precipitation and the precipitation aloft since a radar does not scan all the way down except at close range. Several Z-R relationships had been proposed in the attempt to achieve better accuracy for rainfall estimates by radar system in the tropical climate. Nonetheless, the most accurate Z-R relationship for Malaysia weather radar is yet to be investigated and identified. This paper presents the analyses of previously proposed Z-R relationships for Malaysia weather using new radar data and ground rainfall rate.